Dimensi Kreativitas Filsafat Ilmu Dalam Membangun Ciri Khas Intelektual Muslim - Sarbaini, Albara (Jurnal Dewantara, 2016)
Philosophy of science is the formulation that is consistent and in some sense based on scientific theories are important. According to this view, is the task of the philosopher of science to mengelaborisasikan broader implications of science. Characteristic of Muslim intellectuals include fikir power, sensitive, sharp in analyzing and has constituted with the creative power of faith in God Almighty. This study is a literature that tries to make sense of the philosophy of science in shaping the Muslim intellectual in the world of education. The process of accumulation of the data is done by the use of content analysis for further once collected approached critically with hermeneutic and descriptive methods. It is hoped the data is collected can be reduced and be carefully interpreted in mak-ing Conclusions are not merely descriptive, but are presented in a critical Also format. The hermeneutic method used in interpreting the data is collected is philosophical hermeneutics i.e. a process of interpretation that seeks to produce a new meaning and is not to reproduce the initial meaning.